2019
DOI: 10.1158/1078-0432.ccr-18-0706
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PIM Kinase with PD1 Inhibition Improves Immunotherapeutic Antitumor T-cell Response

Abstract: Purpose: Adoptive T-cell therapy (ACT) of cancer, which involves the infusion of ex vivo-engineered tumor epitope reactive autologous T cells into the tumor-bearing host, is a potential treatment modality for cancer. However, the durable antitumor response following ACT is hampered either by loss of effector function or survival of the antitumor T cells. Therefore, strategies to improve the persistence and sustain the effector function of the antitumor T cells are of immense importance. Given the role of metab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 71 publications
(92 reference statements)
2
47
0
Order By: Relevance
“…The inhibition of PIM can increase the tolerance and persistence of T cells in the tumor microenvironment, and the combined effect with blocking PD-1 can significantly improve efficacy (Fig. 7) [170].…”
Section: Combination Therapeutic Strategy To Enhance T Immune Cell Fumentioning
confidence: 99%
“…The inhibition of PIM can increase the tolerance and persistence of T cells in the tumor microenvironment, and the combined effect with blocking PD-1 can significantly improve efficacy (Fig. 7) [170].…”
Section: Combination Therapeutic Strategy To Enhance T Immune Cell Fumentioning
confidence: 99%
“…These effects were potentiated by the use of an anti-PD1 antibody (triple combination therapy), prolonging mouse survival, decreasing tumor growth and improving T-cell migration. 140 Multiple studies have suggested the use of immunotherapeutics, perhaps alongside PIM inhibitors, to overcome the mechanisms of resistance to treatment and improve the functional outcomes. 27,133 CONCLUDING REMARKS Inhibition of PIM in PCa has attracted much attention as a potential monotherapeutic over the last decade, with growing in vitro, in vivo and early clinical trial data supporting this approach to varying degrees.…”
Section: Pim and Immunotherapymentioning
confidence: 99%
“…Data from Sabatino, et al demonstrate that activating naive (CD8+CD62L+CD45RA+) T cells engineered to express a CD19‐specific CAR with CD3/CD28 in the presence of IL‐7, IL‐21, and the glycogen‐synthase‐3b inhibitor TWS119, enhances metabolic fitness and mediates a robust, long‐lasting anti‐tumor response against systemic acute lymphoblastic leukemia xenografts compared to current CAR T cell expansion protocols. Interestingly, inhibition of proviral integration site for Moloney murine leukemia virus (PIM) kinases, a family of serine/threonine kinases that participate in T cell glucose metabolism, during CD8 T cell expansion can enhance mTORC1, improve the uptake of glucose by CD8 T cells, and increase anti‐tumor effector function . Data from Klebanoff, et al demonstrate that Akt signaling inhibition is compatible with CAR and TCR retroviral transduction of human T cells and promotes a CD62L‐expressing central memory phenotype.…”
Section: Novel Therapeutic Approaches Focused On Improving Til Metabomentioning
confidence: 99%